HBR's 10 must reads on leadership for healthcare - Lee, Thomas H. 1953-; Lenz, Mike; Jones, Carmen Jewel (HBR's 10 must reads, 2025)
Help your team excel.Go from being a good practitioner to being an extraordinary leader of healthcare professionals.If you read (or listen to) nothing else on leadership, listen to these articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones for healthcare leaders to help you and your team excel, maximize performance, and live into your mission.This collection of articles includes "What Makes a Leader?," by Daniel Goleman; "What Makes an Effective Executive," by Peter F. Drucker; "What Leaders Really Do," by John P. Kotter; "Level 5 Leadership: The Triumph of Humility and Fierce Resolve," by Jim Collins; "The Work of Leadership," by Ronald A. Heifetz and Donald L. Laurie; "Teamwork on the Fly," by Amy C. Edmondson; "Who Has the D? How Clear Decision Roles Enhance Organizational Performance," by Paul Rogers and Marcia Blenko; "In Praise of the Incomplete Leader," by Deborah Ancona, Thomas W. Malone, Wanda J. Orlikowski, and Peter M. Senge; "Using the Balanced Scorecard as a Strategic Management System," by Robert S. Kaplan and David P. Norton; "Health Care's Service Fanatics," by James I. Merlino and Ananth Raman; and "Engaging Doctors in the Health Care Revolution," by Thomas H. Lee and Toby Cosgrove.